Fragile elderly, systemic conditions and dental homecare - a mini-review - Alexandre Franco Miranda; Stella Maris de Freitas Lima; Taia Maria Berto Rezende (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
Background: The oral health of elderly patients can be treated at home or in the hospital environment with adaptations. This type of home dental care is possible through the synergistic interactions among several health professionals involved in improving the quality of life of dependent and fragile elderly patients. Scientific articles and bibliographic databases on the dental practice-based study in the elderly were searched and analyzed. Search strategy terms were: home care, geriatric dentistry, dental home care, frail elderly, systemic diseases, Alzheimer's disease and oral health. Inclusion criteria were: published articles in English; articles indexed in databases Pubmed; articles published from 2001 to 2019, totaling 22 references.  Objective: The purpose of this review is to describe a different approach in dentistry that encourages adaptation for home dental care.  Conclusion: Home dental care for dependent elderly people should be prioritized as an interdisciplinary health action, as many problems in the oral cavity have direct interference in the systemic condition and the dental conduct at home should be essential, based on the sharing of clinical decisions between family and entire care team for the frail elderly.